The drifter's wheel - DePoy, Phillip (DePoy, Phillip. Fever Devilin series., 2008)
Fever Devilin, born and raised amongst the hill country folk of the Georgia Appalachians, left home a long time ago and pursued an education, then a career, in the wider outside world. A folklorist by inclination and profession, he left the strange world of academia behind to return to his family-home in the if-anything-stranger mountain town he grew up in. But oddness follows Fever wherever he goes and Blue Mountain, Georgia is no different. When a man shows up at his house, claiming to be over a hundred years old even though he looks like he's in his 30's, Fever is pretty sure his guest is not right. When the man starts to wave a gun around, then falls suddenly asleep immediately afterward, Fever thinks he's both "not right" and "dangerous" and slips out to call the sheriff. The sheriff, Fever's childhood friend, has been hearing reports of this particular vagrant all day but before he can get out there, the man disappears. In the early morning, the body of man that fits the description of the mysterious vagrant is found by the side of the road, shot to death. But, although the body is wearing the same clothes that the vagrant was, it isn't the same person.